Removal of nitrate and sulfate from contaminated water using nanofiltration technology - Ardestani, Seyed Mohsen Hashemi (2016)
Nanofiltration systems are mostly applicable in removing small soluble particles in water. This study focuses on the effect conditions such as feed pressure, flow and contamination concentration on the percentage removal and permeate flux. Nitrate and sulfate are hazardous contaminants in water. To simulate them, potassium salts KNO3 and K2SO4 were used to represent contaminants in water sources. In this study, a pilot plant was constructed to test the performance of nanofiltration. The results revealed that the removal of multivalent ions such as sulfate (S ) ions by NF90 is not totally dependent on the water condition with a removal rate not less than 93%. On the other hand, for monovalent ions such as nitrate (N ), water condition significantly affects the system performance. The membrane performance time was stabilized around 60 minutes after the operation and membrane fouling occurred after 480 minutes. In addition, NF90 can remove more than 500 mg/L of nitrate from the polluted water which make it acceptable for drinking (Cp<50 mg/L). The impact of sulfate with concentrations of 250 mg/L and 1250 mg/L on nitrate removal (250 mg/L) was examined. Findings indicated that the rate of nitrate removals decreased by 6.2% and 30.6% at sulfate concentrations of 250 mg/L and 1250 mg/L respectively. The Response Surface Methodology (RSM) was applied to investigate the interaction effect of parameters on percentage removal and permeate flux as responses. The parameters were manipulated in five ranges in the presence of sulfate (concentration was 1250 mg/L), such that feed nitrate concentrations were 50, 100, 150, 200 and 250 mg/L, feed flow rates were 400, 600, 800, 1000 and 1200 L/h; and feed pressures were 4, 6, 8, 10 and 12 bar. Among all parameters, pressure played a positive role in the procedure in such a way that percentage removal and permeate flux increased by increasing the pressure. Percentage removal increased rapidly in the initial stages but after 10 bar of pressure, it gradually decreased. Flow variations did not significantly affect the removal rate, but it caused an increase in the permeate flux. The increase of nitrate concentration had a negative effect on nitrate removal where nitrate level increased in the permeate stream. Moreover, the flux did not change considerably by increasing nitrate concentration. Interaction effects were studied to find optimal conditions that lead to providing high quality water, saving energy and improving nanofiltration performance in water treatment industry. The optimum condition by RSM for nitrate removal is predicted to be at 10.14 bar, flow 1200 L/h and nitrate concentration 117.73 mg/L. The respective response for nitrate removal was 93.77% and 92.97 (L/m2h) for permeate flux. Predicted results by RSM modeling were verified using experimental results where the two sets of outcomes were closed with an error less than 5%. The findings also indicated that the performance of NF90 is acceptable for removing nitrate and sulfate in polluted water with percentage removals range of 81.74-97.89% and 93.48-100% respectively. Results from this approach are applicable in water treatment procedures to improve nanofiltration performance.